2017
DOI: 10.1007/s12010-017-2499-z
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Removal from Biogas by Cyanobacterium Leptolyngbya sp. CChF1 Isolated from the Lake Chapala, Mexico: Optimization of the Temperature and Light Intensity

Abstract: In the present study, the capacity of the cyanobacterium Leptolyngbya sp. CChF1 to remove CO from real and synthetic biogas was evaluated. The identification of the cyanobacterium, isolated from the lake Chapala, was carried out by means of morphological and molecular analyses, while its potential for CO removal from biogas streams was evaluated by kinetic experiments and optimized by a central composite design coupled to a response surface methodology. Results demonstrated that Leptolyngbya sp. CChF1 is able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
2
8
1
Order By: Relevance
“…QUCCCM 56 showed the second-best carbon capture potential with 186.8 ± 16.0 mg CO 2 L −1 d −1 at 40°C. This is higher than the carbon capture rate found by Choix et al (2017) for Leptolyngbya sp. CChF1 of 159 ± 40 mg CO 2 L −1 d −1 .…”
Section: Carbon Capture Ratecontrasting
confidence: 65%
See 3 more Smart Citations
“…QUCCCM 56 showed the second-best carbon capture potential with 186.8 ± 16.0 mg CO 2 L −1 d −1 at 40°C. This is higher than the carbon capture rate found by Choix et al (2017) for Leptolyngbya sp. CChF1 of 159 ± 40 mg CO 2 L −1 d −1 .…”
Section: Carbon Capture Ratecontrasting
confidence: 65%
“…CChF1 of 159 ± 40 mg CO 2 L −1 d −1 . Besides, Choix et al (2017) based the carbon capture rate on the hypothetical carbon content of 51.4% (Chisti 2007) which is an overestimation according to the findings of the current study, where total carbon values of 44-47% were found for Leptolyngbya sp. QUCCCM 56.…”
Section: Carbon Capture Ratementioning
confidence: 41%
See 2 more Smart Citations
“…observered that Leptolyngbya sp. CChF1 can accumulate biopolymer and has the potential to convert CO 2 from biogas to high value‐added products 116 . However, there are many impacts on microalgae capturing CO 2 in the biogas such as mixing wavelengths and light cycles, but microalgae upgrading biogas is an attractive approach 117 …”
Section: Microalgae‐co2‐biomass Cycle Systemmentioning
confidence: 99%